Well-posedness and exponential stability for the logarithmic Lamé system with a time varying delay - Yazid, Fares; Boulaaras, Salah Mahmoud; Shahrouzi, Mohammad (Mathematical Modelling and Analysis, 2026)
The focus of this paper revolves around the initial–boundary value problem associated with a logarithmic Lamé system within a bounded domain, and incorporating a time-varying delay. We demonstrate the system’s well-posedness through the application of semigroup theory. Subsequently, we establish the existence of global solutions by employing the well-depth method. Furthermore, we establish exponential decay of solutions under adequate constraints concerning the weight of the time-varying delay and the frictional damping.